Sudden Unexpected Death and Alcohol Addiction: Case Report on Disulfiram Use - Kondratavičiūtė, Gabija; Banionis, Dalius; Laima, Sigitas; Chmieliauskas, Sigitas; Vasiljevaitė, Diana; Petreikis, Paulius; Badaras, Robertas (Acta medica Lituanica, 2025)
Background: Disulfiram is a type of medication widely prescribed in order to cease alcohol consumption. When used with alcohol, the ‘disulfiram-alcohol reaction’ occurs, causing nausea and vomiting. Disulfiram blocks alcohol dissolving enzymes thus increasing acetaldehyde concentration and inducing the above-mentioned symptoms. These undesirable symptoms are similar to the side effects that occur to oncological patients after the administration of chemotherapy.Materials and methods: Descriptive research method was used. The literature focusing on alcohol, medications and drug consumption was reviewed.Case report: The primary abstinence at the beginning of treatment with Disulfiram does not guarantee that alcohol usage will not get manifested again at the further stages of treatment. Alcohol addiction forces patients to search for a way to avoid the unwanted reactions. Sometimes, patients tend to be quite ingenious while trying to suppress the arising side effects. In many cases, it involves the usage of additional medication.Conclusions: When alcohol addiction overpowers, the patient tries to reduce the undesirable symptoms and may even die if alcohol is combined with disulfiram. Death may occur due to the cardio and neurotoxic effects of acetaldehyde.
Keywords: forensic science; disulfiram; autopsy; toxicology; pathology